Analisis Efektivitas Penggunaan QRIS sebagai Alat Pembayaran Digital bagi Pedagang Kaki Lima - Palma Juanta; Marshall Aria Bima Ginting Suka (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The rapid development of digital technology has encouraged a shift from cash-based transactions to cashless payment systems, including the use of the Quick Response Code Indonesian Standard (QRIS). This study aims to analyze the effectiveness of QRIS as a digital payment tool for street vendors around Universitas Prima Indonesia (UNPRI), identify the challenges encountered in its implementation, and examine its impact on transaction effectiveness. The research employed a quantitative approach, with data collected through questionnaires distributed to 30 respondents selected using purposive sampling. Data analysis was conducted using validity tests, reliability tests, and simple linear regression analysis. The results indicate that all research instruments were valid, with correlation coefficients exceeding the r-table value (0.361), and reliable, with a Cronbach’s Alpha value of 0.764. The regression analysis produced the equation Y = 11.333 + 0.328X, with a t-value of 3.483 and a significance level of 0.002 (< 0.05). These findings demonstrate that QRIS usage has a positive and significant effect on transaction effectiveness among street vendors. The coefficient of determination (R²) of 0.302 indicates that QRIS usage explains 30.2% of the variation in transaction effectiveness, while the remaining 69.8% is influenced by other factors outside the scope of this study. The main benefits perceived by vendors include ease of use, faster transaction processing, improved payment security, and simplified transaction record-keeping. However, several challenges remain, such as unstable internet connectivity, limited digital literacy, and delayed fund settlement processes.